Melody Analysis of Jepin Selendang Dance Music accompaniment - Melano, Melano (TACET Jurnal Pendidikan dan Kajian Seni, 2024)
Musical accompaniment in a dance performance has an important role. Accompaniment music serves to clarify the accent of the movement in the dance, so that the message of a dance work can be conveyed. The aim is to describe, note and analyze the melody that is found in the accompaniment of the Jepin Selendnang dance music. The method used is descriptive analysis method and uses a musicological approach. Data collection was carried out by conducting observations and interviews with the researcher's data collection tool as the main instrument and using auxiliary instruments in the form of observation sheets and interview guidelines. Checking the validity of the data is done by using the method of triagulation and persistence of observation. The results of this study found that the melody has several forms that are played with repetition. Played on a Bb=Do basic note with the original G minor scale, 4/4 measure and with the Moderato tampon. there are two cadres, namely Authentic cadres and Plagal cadres. This research is expected to increase interest in preserving traditional arts, especially the Jepin Selendang dance music in Siantan Hilir, North Pontianak District.